LBA18Survival and treatment patterns in patients (pts) with locally advanced or metastatic NSCLC treated with epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIS): Analysis of US insurance claims databases. (24th November 2019) - Soo, R; Seto, T; Gray, J E; Karimi, P; Taylor, A; Sawyer, W; Thiel, E; Marchlewicz, E; Brouillette, M
Abstract: Background: Most pts with EGFR mutation-positive (EGFRm) NSCLC develop first-line (1L) EGFR-TKI resistance. Previous analyses of US insurance databases have studied healthcare utilisation and expenditure in pts with EGFRm NSCLC starting first-/second-generation (1G/2G) EGFR-TKIs. We examined treatment patterns and survival rates among pts with locally advanced/metastatic NSCLC, who received 1L 1G/2G EGFR-TKIs, in a retrospective analysis of data from the MarketScan Commercial and Medicare Supplemental databases (all US census regions). We also assessed the effect of central nervous system metastases (CNS mets) on survival rates. Methods: Pts ≥18 yrs with EGFRm NSCLC who received 1L 1G/2G EGFR-TKI were analysed from date of first lung cancer diagnosis (index date) through a variable-length follow-up period. Pts included had ≥1 pharmacy claim for 1G/2G EGFR-TKI on/within 60 days post index, and ≥2 non-diagnostic claims with a diagnosis code for lung cancer within 90 days of each other between 1/1/2015 and 31/3/2018. Excluded: pts receiving chemotherapy suitable for SCLC. Data were stratified by CNS mets status. Data that could be linked to the social security administration (SSA) death file were used for mortality analyses. Results: Of 578 pts (median age 63 yrs, 64% female), 275 (48%) had CNS mets and 303 (52%) had no CNS mets. Of the pts with CNS mets, 149 (54%) discontinued 1L EGFR-TKI, of whom 124 (83%) initiated 2L therapy; 121 (40%) pts with no CNS mets discontinued 1L, 85 (70%) of whom initiated 2L therapy. The most frequently prescribed 1L EGFR-TKI was erlotinib (n = 414, 72%). Overall, at 1L, 6% of pts received an add-on therapy, bevacizumab (n = 17, 3%) being the most common. The most frequent 2L therapy was osimertinib (n = 96, 46%). In pts with available SSA mortality data, unadjusted mortality rates were 138 and 92 deaths per 1000-person-years, for pts with (n = 179) and without (n = 202) CNS mets, respectively. Conclusions: Most pts who discontinued 1L treatment commenced 2L; with osimertinib as most frequent. Pts with no CNS mets had numerically lower mortality rates than pts with CNS mets. Editorial acknowledgement: Charlotte Terry, MSc, from iMed Comms, funded by AstraZeneca in accordance with Good Publications Practice (GPP3) guidelines. Legal entity responsible for the study: AstraZeneca. Funding: AstraZeneca. Disclosure: R. Soo: Honoraria (self), Honoraria (institution), Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Bristol-Myers Squibb; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Research grant / Funding (self): Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Lilly; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Merck; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Novartis; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Pfizer; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Taiho; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Takeda; Honoraria (self), Honoraria (institution), Advisory / Consultancy: Yuhan. T. Seto: Honoraria (self): Astellas, AstraZeneca, Bristol-Myers Squibb, Chugai Pharmaceutical, Eli Lilly Japan, MSD, Nippon Boehringer Ingelheim, Novartis, Ono Pharmaceutical, Pfizer Japan, Taiho Pharmaceutical, Takeda, Thermo Fisher Scientific, ; Research grant / Funding (institution): AstraZeneca, Chugai Pharmaceutical, Eli Lilly Japan, MSD, Nippon Boehringer Ingelheim, Novartis, Pfizer Japan, Takeda, Bayer Yakuhin, Daiichi Sankyo, Kissei Pharmaceutical, LOXO Oncology, Merck Serono. J.E. Gray: Honoraria (self): AstraZeneca, Bristol-Myers Squibb, Takeda, Inviata; Advisory / Consultancy: AstraZeneca, Squibb, Celgene, Takeda, Inviata; Research grant / Funding (institution): Array, Merck, AstraZeneca, Genentech, Boehringer Ingelheim, Bristol-Myers Squibb. P. Karimi: Full / Part-time employment: AstraZeneca. A. Taylor: Full / Part-time employment: AstraZeneca. W. Sawyer: Full / Part-time employment, Full time Contractor: AstraZeneca. E. Thiel: Research grant / Funding (institution): AstraZeneca. E. Marchlewicz: Research grant / Funding (institution): AstraZeneca. M. Brouillette: Research grant / Funding (institution): AstraZeneca.